Evaluation of the influence of orthognathic surgery on articular in skeletal class II patients - GH Firoozeai; H Momeni; SH Shahnaseri (Isfahan University of Medical Sciences, 2008)
Introduction: The purpose of orthognathic surgery is to correct facial deformity and dental malocclusion and to obtain normal orofacial function. However, there are controversies of whether orthognathic surgery might have any negative influence on temporomandibular joint. The purpose of this study was to evaluate the influence of orthognathic surgery on articular disc position and temporomandibular joint symptoms of skeletal CI II patients by means of Magnetic Resonance Imaging. Materials and Methods: Fifteen patients (10 women and 5 men) with skeletal CI II malocclusion, aged 19-32 years (mean 23 years), from the Isfahan Department of Maxillofacial surgery were studied. All received lefort I & bilateral sagittal split osteotomy (BSSO) and all patients received pre- and post surgical orthodontic treatment, Magnetic Resonance Imaging was performed 1 day preoperatively and 3 month post operatively. Statistical analysis of the positional change of the disk was done by Wilcoxon rank sum test. Results: The change of articular disc position after mandibular advancement surgery by means of sagittal split ramus osteotomy was not statistically significant, but it tended to be positioned anteriorly. Conclusion: It can be suggested that orthognathic surgery dose not significantly change the position of the articular disc.Key words: MRI, Articular disk, Orthognatic surgery.